2017
DOI: 10.18276/frfu.2017.88/1-38
|View full text |Cite
|
Sign up to set email alerts
|

THE CONCEPTUAL SCOPE OF THE TERM “NON-FINANCIAL INFORMATION” AS A SOURCE Of DIVERSITY OF NON-FINANCIAL DISCLOSURE Of ENTERPRISES

Abstract: Streszczenie: Cel -Celem opracowania jest prezentacja wniosków z analizy zakresu pojęciowego terminu "informacja niefinansowa". Metodologia badania -Badania oparto na tezie o zróżnicowaniu sprawozdań niefinansowych przedsiębiorstw wskutek odmiennego definiowania informacji niefinansowej. Zastosowano krytyczną analizę odnośnych aktów prawnych oraz piśmiennictwa naukowego, a także wnioskowanie dedukcyjne i indukcyjne. Wynik -Przeprowadzone analiza i wnioskowanie doprowadziły do zdefiniowania informacji niefinans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both in theory and in practice it is extremely difficult to make a clear distinction between financial information and non-financial information. M. Sobczyk makes an attempt to systematise current approaches in this scope [2]. According to the authors, interpretations of the indicated terms should be made not by the source or form of presentation (quantitative, mainly monetary vs. qualitative, difficult to measure), but taking into account information needs of recipients.…”
Section: The Aspects Of Generating Non-financial Information For Sustmentioning
confidence: 99%
“…Both in theory and in practice it is extremely difficult to make a clear distinction between financial information and non-financial information. M. Sobczyk makes an attempt to systematise current approaches in this scope [2]. According to the authors, interpretations of the indicated terms should be made not by the source or form of presentation (quantitative, mainly monetary vs. qualitative, difficult to measure), but taking into account information needs of recipients.…”
Section: The Aspects Of Generating Non-financial Information For Sustmentioning
confidence: 99%